Para politikası beklentilerinin sermaye piyasaları üzerindeki etkisi - Selva Demiralp; Kamil Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2010)
– In this paper, we investigate the responsiveness of financial markets to monetary policy expectations in Turkey. According to the efficient markets hypothesis, financial markets respond to anticipated policy actions prior to a policy announcement. As a result, they are expected to respond only to the unanticipated component of the interest rate change following the announcement. By measuring monetary policy expectations through surveys conducted by the Central Bank of the Republic of Turkey, we find that the bond market behaves in accordance with the efficient markets hypothesis in Turkey in the 2002-2009 period. Our results suggest that the same is not necessarily true for the stock market. We check the robustness of our results to different survey types in the post-2005 period.
Keywords: E44; E52; 330; Monetary policy; Expectations survey; Financial Markets; Geldpolitik; Transmissionsmechanismus; Effizienzmarktthese; Türkei